Simulated Prompt Acceleration of Multi‐MeV Electrons by the 17 March 2015 Interplanetary Shock. Issue 10 (14th October 2017) - Hudson, Mary; Jaynes, Allison; Kress, Brian; Li, Zhao; Patel, Maulik; Shen, Xiao‐Chen; Thaller, Scott; Wiltberger, Michael; Wygant, John
Abstract: Prompt enhancement of relativistic electron flux at L = 3–5 has been reported from Van Allen Probes Relativistic Electron Proton Telescope (REPT) measurements associated with the 17 March 2015 interplanetary shock compression of the dayside magnetosphere. Acceleration by ∼1 MeV is inferred on less than a drift timescale as seen in prior shock compression events, which launch a magnetosonic azimuthal electric field impulse tailward. This impulse propagates from the dayside around the flanks accelerating electrons in drift resonance at the dusk flank. Such longitudinally localized acceleration events produce a drift echo signature which was seen at >1 MeV energy on both Van Allen Probe spacecraft, with sustained observations by Probe B outbound at L = 5 at 2100 MLT at the time of impulse arrival, measured by the Electric Fields and Waves instrument. MHD test particle simulations are presented which reproduce drift echo features observed in the REPT measurements at Probe B, including the energy and pitch angle dependence of drift echoes observed. While the flux enhancement was short lived for this event due to subsequent inward motion of the magnetopause, stronger events with larger electric field impulses, as observed in March 1991 and the Halloween 2003 storm, produce enhancements which can be quantified by the inward radial transport and energization determined by the induction electric field resulting from dayside compression. Key Points: Prompt MeV electron enhancement at L = 3‐5 is seen in Van Allen Probes measurements from 17 March 2015 IP shock magnetopause compression MHD test particle simulations reproduce drift echoes observed by the REPT instrument Azimuthal electric field impulse responsible for acceleration and radial transport is consistent with EFW measurements